C-Reactive Protein in Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy and Relationship with Ventricular Tachycardia - Aimé Bonny; Nicolas Lellouche; Ivo Ditah; Françoise Hidden-Lucet; Martial T. Yitemben; Benjamin Granger; Fabrice Larrazet; Robert Frank; Guy Fontaine (Cardiology Research and Practice)
Background. The relationship between C-reactive protein (CRP) elevation and ventricular tachycardia (VT) in arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C) is unclear. Methods and Results. In 91 consecutive patients with either ARVD/C with or without VT (cases) or idiopathic right ventricular outflow tract (RVOT) tachycardia (controls), blood sampling were taken to determine CRP levels. In ARVD/C patients with VT, we analyzed the association between VT occurrences and CRP level. Sixty patients had ARVD/C, and 31 had idiopathic RVOT VT. Patients with ARVD/C had a significant higher level of CRP compared to those with RVOT VT (3.5±4.9 versus 1.1±1.2 mg/l, P=.0004). In ARVD/C group, 77%, (n=46) patients experienced VT. Of these, 37% (n=17) underwent blood testing for CRP within 24 h after the onset of VT and the remaining 63% (n=29) after 24 h of VT reduction. CRP level was similar in ARVD/C patients with or without documented VT (3.6±5.1 mg/l versus 3.1±4.1 mg/l, P=.372). However, in patients with ARVD/C and documented VT, CRP was significantly higher when measured within 24 hours following VT in comparison to that level when measured after 24 h (4.9±6.2 mg/l versus 3.0±4.4 mg/l, P=.049). Conclusion. Inflammatory state is an active process in patients with ARVD/C. Moreover, there is a higher level of CRP in patients soon after ventricular tachycardia, and this probably tends to decrease after the event.